Association-dissociation dynamics of ionic electrolytes in low dielectric medium - Ghosh, Deborin; Sakpal, Sushil S.; Chatterjee, Srijan; Deshmukh, Samadhan H.; Kwon, Hyejin; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Ionic electrolytes are known to form various complexes which exist in dynamic equilibrium in a low dielectric medium. However, structural characterization of these complexes has always posed a great challenge to the scientific community. An additional challenge is the estimation of the dynamic association-dissociation time scales (lifetime of the complexes), which are key to the fundamental understanding of ion transport. In this work, we have used a combination of infrared absorption spectroscopy, two-dimensional infrared spectroscopy, molecular dynamics simulations, and density functional theory calculations to characterize the various ion complexes formed by the thiocyanate-based ionic electrolytes as a function of different cations in a low dielectric medium. Our results demonstrate that thiocyanate is an excellent vibrational reporter of the heterogeneous ion complexes undergoing association-dissociation dynamics. We find that the ionic electrolytes exist as contact ion pairs, dimers, and clusters in a low dielectric medium. The relative ratios of the various ion complexes are sensitive to the cations. In addition to the interactions between the thiocyanate anion and the countercation, the solute-solvent interactions drive the dynamic equilibrium. We have estimated the association-dissociation dynamics time scales from two-dimensional infrared spectroscopy. The exchange time scale involving the cluster is faster than that between a dimer and an ion pair. Moreover, we find that the dynamic equilibrium between the cluster and another ion complex is correlated to the solvent fluctuations.